2007
DOI: 10.1111/j.1600-0897.2006.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Systemic TNF‐α and IFN‐γ with IVF Treatment Outcome and Peripheral Blood NK Cells

Abstract: The systemic levels of TNF-alpha and IFN-gamma have no association with implantation rate or miscarriage rate in women undergoing IVF treatment. However, high levels of TNF-alpha and IFN-gamma are associated with elevated levels of activated NK cells and this may subsequently exert a negative impact on reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…On the other hand, exposure of large amounts of TNF‐α to pregnant mice causes abortion . For the systemic TNF‐α, it is reported that there are no associations between systemic TNF‐α level and reproductive outcomes, such as implantation failure and recurrent miscarriage . Taken together, uterine NK cell‐derived TNF‐α and IFN‐γ may be important for cell differentiation, angiogenesis, and vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, exposure of large amounts of TNF‐α to pregnant mice causes abortion . For the systemic TNF‐α, it is reported that there are no associations between systemic TNF‐α level and reproductive outcomes, such as implantation failure and recurrent miscarriage . Taken together, uterine NK cell‐derived TNF‐α and IFN‐γ may be important for cell differentiation, angiogenesis, and vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…30 For the systemic TNF-α, it is reported that there are no associations between systemic TNF-α level and reproductive outcomes, such as implantation failure and recurrent miscarriage. [31][32][33] Taken together, uterine NK cell-derived TNFα and IFN-γ may be important for cell differentiation, angiogenesis, and vascular remodeling. Successful function of TNF-α and IFN-γ in pregnancy, therefore, depends on the appropriate regulation and concentration of TNF-α and IFN-γ produced by NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…An immunological basis for "unexplained" implantation failure, miscarriage and late term pregnancy complications/failures has been supported in numerous studies (Beer et al, 1996;Beer and Kwak, 1997;Coulam et al, 1995;Kwak et al, 1998aKwak et al, , 1998bKwak et al, , 2000Kwak-Kim et al, 2003;Ng et al, 2002;Saito et al, 2007;Steinborn et al, 2008;Thum, 2007;Winger et al, 2012). Such cases have often been associated with abnormalities in several different in vitro immune parameters: natural killer cell cytotoxicity, proportion of peripheral blood CD56+CD3− cells, and Th1:Th2 bias.…”
Section: Introductionmentioning
confidence: 90%
“…In women with repeated implantation failure (RIF), increased levels of TNF-a and IFN-c are associated with elevated levels of activated NK cells, and this may subsequently exert a negative impact on reproduction. 8 NK cells are innate immune effector cells and IFN-c production of NK cells is suppressed during normal early pregnancy. 6 It has been reported that dysregulated NK cells results in implantation failure, abortion, and preeclampsia.…”
Section: Introductionmentioning
confidence: 99%